(untitled) (International Seven Journal of Multidisciplinary, 2022)
The use of People Analytics has been transforming the way organizations manage and develop their human capital, providing more assertive decisions aligned with strategic objectives. It is a methodology based on the collection, analysis, and interpretation of data related to employees’ behavior, performance, and potential, enabling Human Resources areas to develop more targeted and effective actions. The application of this approach favors the identification of patterns, the anticipation of needs, and the proposal of customized solutions, increasing competitiveness and innovation within companies. The use of technological tools and statistical models enhances predictive and diagnostic capacity, contributing to the creation of more engaged teams aligned with organizational culture. This transformation is not limited to large corporations, as companies of different sizes and sectors can benefit from data-based analysis to optimize processes and improve employee experience. The integration of People Analytics with strategic management allows for a deeper understanding of organizational demands and the impact of people management actions on corporate results. By linking performance metrics with business indicators, decisions become evidence-based, reducing risks and increasing the effectiveness of implemented strategies. This perspective reinforces HR’s role as a strategic area, capable of directly influencing business growth and sustainability. Thus, People Analytics stands out as an essential tool for the future of people management, enhancing decision-making and strengthening the alignment between talent and organizational purpose.